A Nano-Dose Protocol For Cobb Angle Assessment in Children With Scoliosis: Results of a Phantom-based and Clinically Validated Study. Issue 7 (August 2019) - Pedersen, Peter H.; Vergari, Claudio; Tran, Alexia; Xavier, Fred; Jaeger, Antoine; Laboudie, Pierre; Housset, Victor; Eiskjær, Søren P.; Vialle, Raphäel
Abstract : Study design: This was a prospective validation study with technical notes. Objective: This study aimed to validate a new ultra–low-dose full-spine protocol for reproducible Cobb angle measurements—the "nano-dose" protocol. Summary of Background Data: Scoliosis is a 3-dimensional (3D) deformity of the spine characterized by 3D clinical parameters. Nevertheless, 2D Cobb angle remains an essential and widely used radiologic measure in clinical practice. Repeated imaging is required for the assessment and follow-up of scoliosis patients. The resultant high dose of absorbed radiation increases the potential risk of developing radiation-induced cancer in such patients. Micro-dose radiographic imaging is already available in clinical practice, but the radiation dose delivered to the patient could be further reduced. Methods: An anthropomorphic child phantom was used to establish an ultra–low-dose protocol in the EOS Imaging System still allowing Cobb angle measurements, defined as nano-dose. A group of 23 consecutive children presenting for scoliosis assessment, 12 years of age or younger, were assessed with standard-dose or micro-dose and additional nano-dose full-spine imaging modalities. Intraobserver and interobserver reliability of determining the reliability of 2D Cobb angle measurements was performed. The dosimetry was performed in the anthropomorphic phantom to confirm theoretical radiation dose reduction. Results: A nano-dose protocol was established for reliable Cobb angle measurements. Dose area product with this new nano-dose protocol was reduced to 5 mGy×cm 2, corresponding to one sixth of the micro-dose protocol (30 mGy×cm 2 ) and <1/40th of the standard-dose protocol (222 mGy×cm 2 ). Theoretical dose reduction, for posteroanterolateral positioning was confirmed using phantom dosimetry. Our study showed good reliability and repeatability between the 2 groups. Cobb variability was <5 degrees from the mean using 95% confidence intervals. Conclusions: We propose a new clinically validated nano-dose protocol for routine follow-up of scoliosis patients before surgery, keeping the radiation dose at a bare minimum, while allowing for reproducible Cobb angle measurements.